THE DISPOSITION AND METABOLISM OF SULPHASALAZINE (SALICYLAZOSULFAPYRIDINE) IN MAN - Khan, A; Truelove, S; Aronson, J (1982)
We have investigated the disposition and metabolism of sulfasalazine (SASP) in eight adults with and without inflammatory bowel disease. SASP is poorly absorbed (< 12%) and the half-time measured in the serum, 10.2 h, is probably the half-time of absorption and therefore an overestimate of the true half-time. The apparent volume of distribution is low (< 9 l). Renal and biliary clearance rates are low (5.5 and 2.1 ml min -1 respectively) probably due to a high degree of protein binding. Of the absorbed SASP, two thirds is excreted in the urine and one third in the bile. Most of the SASP reaches the colon and is there split by bacteria, forming sulfapyridine (SP) and 5-aminosalicylic acid (5-ASA). SP is almost completely absorbed and, with its metabolites, is excreted in the urine (SP renal clearance rate 32.1 ml min -1). There is no enterohepatic recirculation. Of the 5-ASA released in the colon at least 25% is absorbed and rapidly eliminated in the urine after acetylation. At least 50% is eliminated in the faeces. There are no differences in disposition characteristics when comparing patients with and without inflammatory bowel disease but the metabolism of SASP is markedly reduced in patients taking antibiotics and after removal of the large bowel.